First Japanese Records of Two Commensal Gobies, Lobulogobius omanensis and Pleurosicya annandalei (Teleostei: Gobiidae), Collected Using Remotely Operated Vehicle - Nozomi Hanahara; Takuo Higashiji; Haruka Sugimoto; Jo Okamoto; Hiromi Morota; Reika Soeya (Species Diversity, 2025)
During a recent deep-sea survey around the Okinawa Islands in the Ryukyu Archipelago, southern Japan, two species of commensal gobies, Lobulogobius omanensis Koumans, 1944 and Pleurosicya annandalei Hornell and Fowler, 1922, were observed using remotely operated vehicles (ROVs) on or within marine invertebrates at depths of 95–110 m, and were subsequently collected. This represents the first record of these two species in Japan. This study provides a detailed morphological description of the specimens, including their coloration when alive and fresh. DNA analysis was also performed to further characterize these species. The integration of morphological and genetic approaches is essential for the accurate identification of newly discovered species, particularly in underexplored deep-sea environments.